Spirometric reference values for a caucasian Portuguese adult population: a pilot study - Carvalho, Sandra (2022)
Introduction – The adequacy of the reference values in spirometry ​​is necessary for a correct diagnosis and follow-up of the respiratory pathology. For this reason, and in accordance with international recommendations, locally derived reference equations may be required. Objective – It is intended to estimate reference equations for FEV1 and FVC from a sample of individuals living in Vila Franca de Xira and to compare the values ​​estimated by the European Coal and Steel Community (ECSC) and Global Lung Function Initiative equations (GLI). Methods – Adult volunteers, Caucasians, residents in Vila Franca de Xira, and non-smokers, without respiratory pathology or professional exposure of risk, were included, and excluded high competition athletes and blow instrumentators. Results – Spirometric values ​​of 64 individuals, 20 men (mean age 45`18.8 years; height 1.72`8cm; weight 76.9 `12.6Kg; body mass index 25.8`3.12Kg/m2) e 44 women (mean age 45`12.6 years; height 1.60`6.25cm; weight 67.3 `13.0Kg; body mass index 26.5`5.39Kg/m2) were used to derive reference equations for FVC and FEV1. The estimated values ​​were significantly different from the values ​​predicted by the ECSC equations for FVC and FEV1 in women (p<0.001; p<0.01) and for FVC in men (p<0.001); and were also significantly different from those predicted by GLI for FVC in men and woman (p<0.05; p<0.001). Conclusion – Reference equations were estimated for the Vila Franca de Xira population, which, when compared with the ECSC and GLI equations, presented statistically significant differences. Thus, the importance and contribution of this study to the interpretation of spirometry are evidenced.